Problem-Based Learning Model for Mathematical Problem Solving Ability: Is it Effective for High School Students? - Noeruddin, Ali; Rahmawati, Rinna (IKIP PGRI Bojonegoro, 2025)
This research aims to find out the effectiveness of problem-based learning model on mathematical problems solving ability of the tenth grade students in SMA Negeri 1 Kedungadem, Bojonegoro. The research method used is a quasi-experiment with a non-equivalent control group design. The sampling technique in this study was a cluster random sampling involving 2 classes consisting of 35 students for the experimental class and 35 students for the control class. The instrument used in this research was a test (include pre-test and post-test) of students' mathematical problem solving ability in the form of essay questions. The results showed that the class taught by problem-based learning model had an average score of 82.6, while the control class had an average score of 73.57. Furthermore, in Independent Sample T-Test, the calculated value>t- table (4.033> 2.007) means that H0 is rejected and Ha is accepted. Then, it can be concluded that problem-based learning model is effective in improving mathematical problems solving ability of the tenth grade students of SMA Negeri 1 Kedungadem, Bojonegoro.